Contribution of StockMarket Towards Economic Growth: An Empirical Study on Bangladesh Economy - Sonia Rezina; Nusrat Jahan; Mohitul Ameen Ahmed Mustafi (European Scientific Journal, ESJ, 2017)
The economic growth of a country is influenced by many different factors. This study aims to investigate the causal relationship between stock market development and economic growth in Bangladesh as well as the impact of stock market performance upon the economic growth of Bangladesh. The stock market performance has been measured by market capitalization ratio, number of listed companies, total value traded and turnover ratio; and the economic growth was represented by real gross domestic product. The periods taken for study were from year 1994 to year 2015.The effect of the stock market reform will also be addressed to explain the relationship. The study has been conducted using Augmented Dickey- Fuller Unit Root Test, Johansen Cointegration Test and the Granger Causality Test. The findings of the research should help the policy makers and regulators to look after their interest in the financial sector of the country.